Approaches for the study of leaf carbohydrate metabolic compartmentation in arabidopsis thaliana - Fly, Richard Derek (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2010.